Desarrollo de un módulo virtual inmersivo para el entrenamiento del control de procesos de flujo. - Escobar Artieda, Geovany Alexander (2021)
The analysis of Control Systems is very important because fully automatic machines are currently being developed, therefore it is becoming more and more important in daily life and even more so in the industrial sector, in the continuous processes of large companies it is difficult to analyze and experimentation, for this reason requires training through didactic modules. Currently, the Instrumentation and Control Laboratory does not have an immersive virtual flow control module in which it is possible to experiment with different mathematical models in order for the student to analyze and study the behavior of the flow variable in a Virtual environment. This project aims to virtualize a didactic module of a flow process, which is developed in two stages, the first is to model the plant in CAD software, then import it into Unity to create an immersive environment that works with virtual reality glasses where the person is involved in the process in order to analyze its behavior, the second stage is the design of controllers to apply in the virtual flow control. For this, the mathematical model is used, linking the instrumentation software with the Unity graphic engine for correct operation, additionally an external display will be implemented using Arduino Uno to observe data from the flow process. The flux behaves in a stable way in all the reference values or set point that was added to the system, the virtual reality glasses communicate effectively with the computer for the correct immersion. The Tcp/Ip communication between the two software works correctly and the whole system comparing with the real module has a similarity of 99.99%.